PRACTISING AND IMPROVING THE 1 VS: 1 SITUATIONS - Vitucci, Francesco (Sport- és Egészségtudományi füzetek, 2026)
The rules of 1on1 Every basketball system requires discipline, execution, reading, creativity, and individual responsibility. Whatever we set on offence for our players, at the very end, we are all looking for easy layups, spot-up shots, three-pointers or free throws. To achieve this goal, our players must always attack the rim; therefore, they should be good 1-on-1 players. In terms of discipline and execution of the play, one of our rules is only to break the execution of the play if there is a clear opportunity to score. A clear chance in our system means a layup or an open spot up shot. Regardless of this rule, our players must be ready to punish any defensive mistake with a good 1-on-1 offence. We try to create situations when the ball is moving, and we have an advantage: the point when the ball player must attack without hesitation. With a good read and drive, the ball player can create several options for every player on the floor. Not every player can play high quality 1on1, but our philosophy is that the players must know their limits and work on them to reach a higher level.